Experimental and numerical analysis of flexural composite beams with partial use of high strength/high performance concrete - Lapko, Andrzej; Sadowska‐Buraczewska, Barbara; Tomaszewicz, Andrzej (Journal of Civil Engineering and Management, 2005)
The paper summarises the experimental and numerical analysis of flexural capacity and deformability of structural concrete beams prepared as composite members consisting of two concrete layers made of reinforced normal concrete and high‐performance concrete (HPC). The reinforced concrete composite beams used in the tests were prepared in full scale with the cross‐section of 120 × 200 mm and the effective span of 2950 mm. The basic samples were composed in two layers consisting of high‐performance concrete as the top layer, and normal strength concrete. The results of the analyses confirm a significant improvement of structural properties of composite beams in comparison to the beams prepared totally of normal concrete, and in some cases also in comparison with the beam totally made of HPC. Stipriojo labai funkcionalaus betono lanksčių kompozitinių sijų eksperimentinis ir teorinis tyrimas Santrauka Pateikiami iš normalaus stiprio bei labai funkcionalių betonų pagamintų kompozitinių sijų eksperimentinės bei teorinės analizės rezultatai. Bandymai buvo atlikti su 120 x 200 mm skerspjūvio ir 2 950 mm tarpatramio gelžbetoninėmis kompozitinėmis sijomis. Pagrindiniai bandiniai buvo pagaminti iš dviejų sluoksnių: iš labai funkcionalaus betono (viršutinėje skerspjūvio dalyje) bei normalaus stiprio betono. Analizės rezultatai parodė kompozitinių sijų ir sijų, pagamintų vien tik iš normalaus stiprio betono, esminius savybių bei elgsenos skirtumus. Palyginti rezultatai, gauti išbandant sijas, pagamintas vien tik iš labai funkcionalaus betono. Raktiniai žodžiai: kompozitinė sija, labai funkcionalus betonas, laikomoji galia, deformavimas, natūralaus dydžio sijos bandymai. First Published Online: 14 Oct 2010